Recrystallization and grain growth of cold-drawn gold bonding wire - Cho, JH; Cho, JS; Moon, JT; Lee, J; Cho, YH; Kim, YW; Rollett, AD; Oh, KH (MINERALS METALS MATERIALS SOC, 2003)
Recrystallization and grain growth of gold bonding wire have been investigated with electron back-scatter diffraction (EBSD). The bonding wires were wire-drawn to an equivalent strain greater than 11.4 with final diameter between 25 and 30 mum. Annealing treatments were carried out in a salt bath at 300 degreesC, and 400 degreesC for 1, 10, 60 minutes, and 1 day. The textures of the drawn gold wires contain major 111), minor (100), and small fractions of complex fiber components. The 100) oriented regions are located in the center and surface of the wire, and the complex fiber components are located near the surface. The (111) oriented regions occur throughout the wire. Maps of the local Taylor factor can be used to distinguish the 111 and 100) regions. The 111) oriented grains have large Taylor factors and might be expected to have higher stored energy as a result of plastic deformation compared to the (100) regions. Both (111 and 100 grains grow during annealing. In particular, 100) grains in the surface and the center part grow into the (111 regions at 300 degreesC and 400 degreesC. Large misorientations (angles >40 deg) are present between the (111) and (100) regions, which means that the boundaries between them are likely to have high mobility. Grain average misorientation (GAM) is greater in the 111 than in the 100) regions. It appears that the stored energy, as indicated by geometrically necessary dislocation content in the subgrain structure, is larger in the (111) than in the 100 regions.
Keywords: LATTICE ORIENTATION; REPRESENTATION; ALUMINUM